Metaphylactic effect of minerals on the immune response, biochemical variables and antioxidant status of newborn calves - Tomasi T.* (2018)
© 2018 Blackwell Verlag GmbHThe aim of this study was to evaluate whether injectable zinc and copper affect host immune responses and antioxidant status of newborn calves. For this study, 19 newborn calves were divided into two groups. The control group consisted of 10 animals; and the treated group consisted of nine animals that received copper edetate (Cu-ed) and zinc edetate (Zn-ed) subcutaneously at the first day of life at doses of 0.3 mg/kg and 1.0 mg/kg respectively. Blood and faecal samples were collected for laboratory analyses (seric biochemistry, proteinogram, antioxidant enzymes and parasitological examination) on days 10, 20 and 30 after birth. On day 10, treated animals showed increased levels of total proteins, as well as increased globulin levels compared to the control group, a finding probably related to the increase in ceruloplasmin and IgG heavy chain. Thirty days after mineral metaphylactic administration, IgG light chain and acid glycoprotein levels significantly increased in treated animals (p <.05). There were no significant differences between groups regarding the biochemical analyses (triglycerides, cholesterol, glucose and urea). On the other hand, the superoxide dismutase and catalase activities increased on day 10 after treatment. In the control group, eight animals showed severe diarrhoea and one died 8 days after birth. Two animals from this group showed mild diarrhoea. Only three treated animals had severe diarrhoea, and six showed signs of mild diarrhoea. All animals that showed severe diarrhoea (control = 8; treated = 3) had hyperthermia (over 39.5°C), and therefore, antibiotic therapy was administered (sulfadiazine and trimethoprim) for five consecutive days. In summary, Zn-ed and Cu-ed decreased the frequency and intensity of diarrhoea, modulated superoxide dismutase (SOD) and catalase (CAT) enzymes and also heightened the immune responsiveness of newborn calves, suggesting a new approach to improve cattle performance and minimize the occurrence of diarrhoea.